Japanese spirituality - Suzuki, Daisetz Teitaro (Japan Society for the Promotion of Science, 1972)
This book consists of the following many parts: japanese spirituality and the kamakura Period, manifestations of Japanese spirituality, Honen and Nembutsu Shomyo, the Myokomin.